Accelerated bone defect regeneration through sequential activation of the M1 and M2 phenotypes of macrophages by a composite BMP-2@SIS hydrogel: An immunomodulatory perspective. (15th August 2022) - Tan, Jie; Zhang, Qing-Yi; Song, Yu-Ting; Huang, Kai; Jiang, Yan-Lin; Chen, Jun; Wang, Rui; Zou, Chen-Yu; Li, Qian-Jin; Qin, Bo-Quan; Sheng, Ning; Nie, Rong; et al.
Abstract: The immune response of the host towards foreign body, especially in the form of giant cell reaction against the implanted materials, is a vital factor for determining the repair outcome of bone defect. Biomaterials with good immunomodulatory capacity and suitable degradation may promote the regeneration of bone defect and osteointegration with the host. Small intestine submucosa (SIS), a decellularized material, has been shown to possess a property for inducing the M2 phenotype of macrophages. Our findings suggested that the SIS hydrogel could induce the macrophages to polarize into mixed M1/M2 phenotypes, and such phenotypes have enhanced the migration and tube formation of angiogenesis-associated cells in vitro, whilst having a mild effect on osteoclastogenesis and osteogenesis. Experiment with a rat model for critical-sized bone defect regeneration further demonstrated that the composite BMP-2@SIS hydrogel could sequentially activate M1 and M2 macrophages and promote early-stage angiogenesis, which altogether expedited final bone defect regeneration.